Sosioeconomic, Behavioral, and Biological Determinants of Tuberculosis Incidence: A Case Study in Aceh Besar, Indonesia - Farrah Fahdhienie; Akbar, Fahrisal (Journal of Public Health and Pharmacy, 2025)
Introduction: Tuberculosis (TB) pandemic is a significant global health concern, especially in low- and middle-income countries. Every year the incidence and deaths due to TB continue to increase. Preventing and controlling TB effectively requires understanding the complex interplay of the multidimensional TB risk factors, which consist of social, behavioral, and biological determinants that contribute to its spread. This study aimed to identify and analyze the primary risk factors associated with TB incidence. Methods: This study employed a case-control design with 44 respondents consisting of 22 laboratory-confirmed TB patients and 22 non-TB patients with matching ages and sex. This study used a structured questionnaire was used to collect data through face-to-face interviews. The questionnaire assessed risk factors across three key domains: social determinants, behavioral determinants, and biological determinants. Bivariate analysis, which used a chi-square test (p-value <0.05), and multivariate analysis, which used a logistic regression test, were performed to determine risk factors most associated with TB incidence. Results: Low income (p-value=0.015;OR=6.923;95%CI=1.285-37.287), high TB-related stigma (p-value=0.033;OR=3.852;95%CI=1.086-13.661), insufficient TB knowledge (p-value =0.033;OR=3.852;95%CI=1.086-13.661), food insecurity (p-value=0.006;OR=5.950;95%CI=1.586-22.328), lack of preventative measures (p-value=0.015;OR=4.667;95%CI=1.299-16.761), history of contact with TB patients (p-value =0.039;OR=7.875;95%CI=0.860-72.122), and presence of comorbidities (p-value =0.031;OR=5.714;95%CI=1.051-31.072) were significantly associated with TB incidence. Comorbidities emerged as the strongest risk factor (p-value =0.020; OR=12.141;95%CI=1.486-99.231). Conclusion: This study highlights several major factors influencing TB incidence, including social, behavioral, and biological determinants. The findings suggest that effective TB control strategies should address socioeconomic conditions, promote healthy lifestyles, and involve community leaders and TB survivors in educational campaigns, stigma reduction, and early diagnosis efforts. Understanding these health determinants can inform more targeted public policies for curbing TB incidence.